Adaptação de um motor diesel para atuar como bicombustível: diesel-gás natural - Macêdo, Rennan Jackson Ferreira (2018)
Brazil figures as one of the greatest consumers of electric power in the world, being third in the American continent, surpassed only by the United States and Canada. The largest consumer of electricity in Brazil is the industrial sector, followed by residential and commercial, with 35.7%, 28.8% and 19.1%, respectively. In this way, the industrial sector is most affected by problems of energy supply. In order to reduce costs and guarantee the supply of electricity at times of more expensive tariffs, industries usually make use of generator sets powered by engines that use diesel. These engines, however, contaminate the environment due to the emission of large amounts of particulate matter and sulfur compounds in their exhaust gases. In this context, new fuels have been studied for use in diesel engines, such as natural gas. In this sense, this paper aims to adapt a MWM diesel engine, model D229-4 to act in a Dual way with diesel and natural gas. In this adaptation, the main objective was to reduce the operation costs of the engine, as well as the reduction of the emission of particulates to the environment. After performing the tests and comparing the results of the original engine with those of the dual engine, it was possible to verify a cost reduction of operation of up to 17.92 R$ per hour, considering that there is variation in the percentage of economy, that goes from 3.49% to 48.77%, depending on the applied load. Another important factor was the reduction of the opacity of the smoke originated during combustion. In this way, the set of results obtained certifies that the conversion of Diesel engines to Dual mode (diesel / natural gas) is economically viable and provides a considerable reduction in pollution of the environment.